2004
DOI: 10.1038/sj.bmt.1704613
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with autologous stem cell transplantation in patients with oligometastatic breast cancer

Abstract: Summary:The purpose of this prospective trial was to study a combined-modality treatment including local consolidation by surgery or radiotherapy and high-dose chemotherapy (HDC) followed by peripheral-blood stem-cell (PBSC) transplantation. In all, 48 patients with oligometastatic breast cancer amenable to local treatment after induction chemotherapy with epirubicin and cyclophosphamide or paclitaxel and cisplatin, depending on prior adjuvant chemotherapy, were enrolled. The median follow-up was 41 months (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Epirubicin and cisplatin are largely employed in the cancer treatment of these neoplasms, so that the high-dose epirubicin and cisplatin combination might be considered in the mobilization phase of novel HDC regimens. [1][2][3][21][22][23] In our study, a mobilizing course of high-dose epirubicin and cisplatin followed by three PBPC-supported HDC courses with high doses of carboplatin and paclitaxel was associated with either a rapid hematopoietic reconstitution after each HDC course or a significant peripheral neurotoxicity at the end of treatment. Results of two phase II trials in patients with NSCLC showed that the combination of carboplatin (AUC ¼ 6) and paclitaxel (200-225 mg/m 2 ) is feasible with granulocyte CSF employed in 28-31% of courses and grade 3 peripheral neurotoxicity in 10-20%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epirubicin and cisplatin are largely employed in the cancer treatment of these neoplasms, so that the high-dose epirubicin and cisplatin combination might be considered in the mobilization phase of novel HDC regimens. [1][2][3][21][22][23] In our study, a mobilizing course of high-dose epirubicin and cisplatin followed by three PBPC-supported HDC courses with high doses of carboplatin and paclitaxel was associated with either a rapid hematopoietic reconstitution after each HDC course or a significant peripheral neurotoxicity at the end of treatment. Results of two phase II trials in patients with NSCLC showed that the combination of carboplatin (AUC ¼ 6) and paclitaxel (200-225 mg/m 2 ) is feasible with granulocyte CSF employed in 28-31% of courses and grade 3 peripheral neurotoxicity in 10-20%.…”
Section: Discussionmentioning
confidence: 99%
“…Epirubicin and cisplatin are two of the most active and largely employed drugs in cancer treatment, so that the combination of high-dose epirubicin with cisplatin plus filgrastim could represent an ideal mobilizing regimen for clinical trials with HDC and PBPCs in several neoplasms. [2][3][4] In a previous study from our institution, epirubicin (150 mg/m 2 ) followed by filgrastim was tested as a single mobilizing chemotherapeutic agent in patients with early or first-line metastatic breast cancer. 9 Patients were mobilized after 1-3 courses of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past years, however, it has been clearly demonstrated that improvement of local control impacts on survival in locoregionally confined disease. Results from a variety of retrospective investigations suggest that even in breast cancer the addition of local therapy (especially radiation therapy) to metastatic sites may be associated with better survival [20,21]. In the analysis by Nieto et al [20], the addition of radiotherapy to metastatic lesions was the only therapy-related prognostic factor in patients undergoing intensive chemotherapy for relapsed breast cancer (table 3).…”
Section: Local Therapy In Metastatic Breast Cancermentioning
confidence: 99%
“…They might only be detected with follow-ups which allow imaging diagnostic procedures, even in the case of asymptomatic disease [10]. In the case of still localised metastasis, one option is surgical intervention, together with systemic therapies when necessary [11,12]. In terms of metastasis resection, by which a 'no evidence of disease' status can be achieved, there are only nonrandomised studies for metastatic breast cancer.…”
mentioning
confidence: 99%